Radiative water-cooling in maritime and moderate continental climatic conditions - Balen, Igor (Strojniški vestnik, 2005)
In this paper, the analysis of a flat-plate radiative panels operation, using average hourly weather data, was conducted. Radiative panels, with high-emittance surface cover, were integrated in the space-ventilation system with air-cooling by means of a cold-water coil. The panels should prepare a sufficient quantity of cold water that is collected in a cold-water tank during the nighttime operation. The collected cold water is used for cooling of the air during daytime. A simulation model for the parametric analysis of the system in summer operating conditions and the influence of its components on the system's operation was developed. The model includes the control of the system's operation, which prevents water circulation in the periods without cooling contributions. The purpose of the research was to predict the system behaviour in the Irish and the continental Croatian climatic conditions, to enable sizing and design of the test rig that is to be built for experimental validation of the system. The results of simulation were obtained for the small cooling system with a total panel aperture area of 6 m2and a volume of tanks of 300 l. The results were presented in the charts, where the influence of the main parameters on the system's operation was illustrated.The results showed that the radiative cooling system is more efficient in maritime than in moderate continental climatic conditions during summer.
Keywords: sistemi hladilni; pogoji klimatski; metode eksperimentalne; hladilni sistemi; klimatske naprave; termične lastnosti; matematični modeli